2021
DOI: 10.1002/clc.23718
|View full text |Cite
|
Sign up to set email alerts
|

Elevated serum lipoprotein(a) is significantly associated with angiographic progression of coronary artery disease

Abstract: Background Lipoprotein(a)[Lp(a)] has been considered as an independent risk factor for coronary artery disease (CAD). The present study aimed to evaluate the association between baseline serum Lp(a) and CAD progression determined by angiographic score. Methods A total of 814 patients who had undergone two or more coronary computed tomography angiography at least 6 months apart were consecutively enrolled and the coronary severity was determined by the Gensini score system. Patients were stratified into two gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…The results showed that the levels of Lpa and APO-B in CIS patients were positively correlated with the degree of MCA stenosis, and the APO-A level was negatively correlated with the degree of MCA stenosis. It has been reported by Shui et al [ 22 ] that the increase in Lpa is positively correlated with the progression of coronary artery disease. Yaseen et al [ 23 ] reported that APO-B was positively correlated with the degree of coronary artery disease.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the levels of Lpa and APO-B in CIS patients were positively correlated with the degree of MCA stenosis, and the APO-A level was negatively correlated with the degree of MCA stenosis. It has been reported by Shui et al [ 22 ] that the increase in Lpa is positively correlated with the progression of coronary artery disease. Yaseen et al [ 23 ] reported that APO-B was positively correlated with the degree of coronary artery disease.…”
Section: Discussionmentioning
confidence: 99%
“…6 In addition, Lp(a) was shown to be associated with progression of coronary artery plaque assessed with a semiquantitative CCTA score, independent of cardiovascular risk factors. 7 CCTA has also provided insight in to the relationship between Lp(a) levels and coronary plaque progression demonstrating that Lp(a) is associated with progression of low attenuation plaque (necrotic core), but not total, calcified, or noncalcified plaque. 8 In the current study, limited quantitative plaque analysis was performed with only total plaque burden and not the burden of the different plaque subtypes assessed.…”
Section: See Article By Dai Et Almentioning
confidence: 99%
“…2 Previous studies have confirmed that patients with IBD present with dyslipidaemia, 3 4 which is a well-established risk factor for cardiovascular disease. Several studies have shown that lower total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), apolipoprotein B (Apo B) and apolipoprotein A-I (Apo A-I) levels are associated with higher triglyceride (TG) and lipoprotein (a) (Lp(a)) levels in patients with IBD, [5][6][7][8][9][10] which are independently associated with more severe disease. 7 9 10 Additionally, compared with the general population, male patients with IBD have higher TG levels, while female patients with IBD have significantly lower TG levels.…”
Section: Introductionmentioning
confidence: 99%